General Characteristics of the Proceedings Carried out in the Absence of the Accused (Trial in Absentia) - Hovhannisyan, Armen (Bulletin of Yerevan University C: Jurisprudence, 2022)
In the submitted article, the author has discussed the compliance of in absentia proceedings as an institution that is being introduced to the criminal procedure system of the RA with the Constitution of the RA and international standards. Based on the research of the case law of international bodies and practice of other states, as well as having analyzed the provisions of the Criminal Procedure Code of the RA aimed at regulating in absentia proceedings and the legal guarantees provided to the accused, the author has come to the conclusion that the possibility of holding in absentia proceedings provided for in the Criminal Procedure Code of the RA not only complies with international standards, but also derives from the requirement of ensuring the constitutional and convention right to a fair trial.
Keywords: in absentia proceeding; trial in absentia; proceedings carried out in the absence of the accused; right to a fair trial; right to defend oneself